Правовий статус регіону в Україні та його конституційне закріплення - Барбашова, Наталія Володимирівна; Барбашова, Наталья Владимировна; Barbashova, Natal'ja (Одеса : Юрид. л-ра, 2012)
The problem of optimization of the administrative-territorial structure of Ukraine was studied from the standpoint of the environmental law in the constitutional process which occurs in the country nowadays. It was founded that the decentralization of public authority in Ukraine and strengthening constitutional status of regions with legislative powers are essential.
Барбашова Н. В. Правовий статус регіону в Україні та його конституційне закріплення / Н. В. Барбашова // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 45-52.
Keywords: право; Конституція України; охорона довкілля; децентралізація; регіон; компетенція; Конституция Украины; охрана окружающей среды; децентрализация; регион; компетенция; law; the Constitution of Ukraine; the environment; decentralization; region; competence